2018
DOI: 10.1177/1833358317749369
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of health provider readiness for telemedicine services in Uganda

Abstract: Health provider readiness to integrate telemedicine services varies at the different levels of the health facility and job title or role. However, referral hospitals and administrators were more likely to integrate telemedicine than HC-IVs and doctors, respectively. While this study shows physicians and administrators are ready, other sectors (nurses, allied healthcare workers, public) will also need to be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
15
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 23 publications
(24 reference statements)
11
15
1
1
Order By: Relevance
“…Securing patient data involves protecting confidential medical information and once security is compromised, it creates a sense of fear and resistance among users. Similar to this study, concerns over privacy and security being compromised have been raised in several other studies [6], [44], [39], [38], [10], [54] as barriers of eHealth adoption. In a study conducted by Chang [42], participants expressed concerns about the confidentiality and the security of patient data with smartphones, with specific concern on multimedia capabilities that were perceived as having the potential of abuse.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Securing patient data involves protecting confidential medical information and once security is compromised, it creates a sense of fear and resistance among users. Similar to this study, concerns over privacy and security being compromised have been raised in several other studies [6], [44], [39], [38], [10], [54] as barriers of eHealth adoption. In a study conducted by Chang [42], participants expressed concerns about the confidentiality and the security of patient data with smartphones, with specific concern on multimedia capabilities that were perceived as having the potential of abuse.…”
Section: Discussionsupporting
confidence: 76%
“…Training has been identified as one of the key success factors in technology acceptance. Commensurate to our findings, receiving necessary training prior to using the system has been encouraged in several other studies [6], [38], [44], [19], [28], [21], [40], [30], [33]. Training equips users with the knowledge of the system [20], gives a chance to acclimate to the new processes and in the long run boosts confidence to use the system.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The magnitude of remote consultation activity is difficult to estimate [9,10]. Various studies in developed as well as in developing countries examined the acceptance of HCPs and patients to the concept of remote consultations especially in rural areas [11,12]. A Questionnaire based assessment in Spain [11] and another in Uganda [12] confirmed that the HCPs are willing to implement remote consultations as an alternative to face to face consultations.…”
Section: Comparison With Coexisting Literaturementioning
confidence: 99%
“…Cultural barriers such as digital divide, digital illiteracy, awareness gap, socio-cultural differences, perceptions, and resistance to change. [ 33 ] Cross-sectional Uganda Tele-education The unavailability of telemedicine regulations and policies in the country. [ 34 ] Perspective Africa Tele-education, telecardiology,tele-ultrasonography, teledermatology, telepsychiatry, tele-ophthalmology and rehabilitation Legal and ethical issues [ 35 ] Perspective Africa Teleneurology Financing costs, Ethics Issues, data protection policies and budgetary allocation [ 36 ] Supplementary Zimbabwe Teleconsultation, tele-monitoring, and tele-expertise (Obstetrics and Gynaecology) Lack of technological devices, network connectivity and digital illiteracy.…”
Section: Discussion Of Resultsmentioning
confidence: 99%